Signalling of Coherence Relations in Discourse, Beyond Discourse Markers. Issue 8 (17th November 2018) - Das, Debopam; Taboada, Maite
ABSTRACT: We argue that coherence relations (relations between propositions, such as Concession or Purpose ) are signalled more frequently and by more means than is generally believed. We examine how coherence relations in text are indicated by all possible textual signals, and whether every relation is signalled. To that end, we conducted a corpus study on the RST Discourse Treebank, a corpus of newspaper articles annotated for rhetorical (or coherence) relations. Results from our corpus study show that most relations in text (over 90%) are signalled and also that most signalled relations (over 80%) are indicated not only by discourse markers ( and, but, if, since ), but also by a wide variety of signals other than discourse markers, such as reference, lexical, semantic, syntactic and graphical features. These findings suggest that signalling of coherence relations is much more sophisticated than previously thought.